IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KABUPATEN TABANAN NOMOR 11 TAHUN 2012 TENTANG RENCANA TATA RUANG WILAYAH KABUPATEN TABANAN TAHUN 2012-2032 DALAM MENGENDALIKAN ALIH FUNGSI LAHAN SAWAH (STUDI KASUS KECAMATAN MARGA) - Astrini Jeger, Kadek Mira; Yudartha, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2018)
ABSTRACT Marga District has good potential for the agricultural sector, however, there was aonversion of 190 ha of rice fields in 2016. It causes a discrepancy in irrigated agricultural designation stipulated in the Tabanan District Regulation No. 11 of 2012 with the current area of ??agricultural land in the District of Marga. This study will discuss the performance of Tabanan District Regulation No. 11 of 2012 in controlling the conversion of rice fields in Marga District by using qualitative exploratory methods and using Policy Implementation Theory from Van Meter and Van Horn including standards and objectives, resource, communication between organizations, characteristics of implementing organizations, economic, social and political conditions and the attitude of the implementers. Result showed that the performance of Tabanan Regency Regional Spatial Planning policy in controlling the conversion of rice fields in Marga Subdistrictince the RDTR of Marga District has not been completed. It was caused by the lack of employees who understand the spatial layout in Tabanan District Government. Besides, rapid economic and population development in Marga Subdistrict also has an impact on the decrease of rice fields area. Keywords: Implementation, Spatial, Tabanan